Perjuangan Rakyat dalam Mempertahankan Kemerdekaan Indonesia Pada Agresi Militer II 1948-1949 di Pulau Jawa - Anita Safitri (Program Studi Pendidikan Sejarah Universitas Riau, 2023)
The Proclamation of Indonesian Independence was promulgated on 17 August 1945. Nevertheless, this had not yet freed Indonesia from the colonial grip in September 1945 the Dutch came back to Indonesia by leaking allied troops who had then won World War II. This study was conducted using historical methods to obtain a truth from past events regarding the people's struggle during the Second Dutch Military Aggression on Java Island. The result of this study was the Second Dutch Military Aggression carried out in 1948–1949 with the focus of its attacks on Java and Sumatra. Resistance on Java was guerrilla by Indonesian military leaders and people who rejoiced to join the militia. In West Java the struggle was fought by the Siliwangi Division and other military leaders, in Central Java the struggle was fought by the guerrilla forces of General Sudirman and its military members as well as in East Java. This guerilla strategy successfully disrupted Dutch defenses in Indonesia. Until the Treaty of Roem-Royen was signed as a form of truce and military aggression in Indonesia.